Model Penataan Lahan Penanggulangan Erosi Berbasis Masyarakat Di Kawasan Danau Batur - Nada, I Made; Redana, I Wayan; Dharma, I G B Sila; Yana, A A Gde Agung (Bumi Lestari; Vol 18 No 1 (2018)DO - 10.24843/blje.2018.v18.i01.p01, 2018)
Erosion control in the community-based Lake Batur area is directed to maintain the balance of Lake Batur. Erosion triggered by the pattern of management of agricultural lands less attention to aspects of soil and water conservation. The purpose of this research is; (1) to obtain a community-based erosion control model, (2) Land management Mapping on the edge of the lake, (3) erosion control strategy at the edge of the lake. This research field experiment and surpei, sampling is done by purposive sampling with amount of 64 sample. The socio-economic support data of the community was determined by 180 respondents in cluster sampling. Interviews and questionnaires are closed questions on a conventional scale. The characteristics of the lake were analyzed descriptive statistics using the SPSS tool. Land mapping is done by GPS method with GIS device. Predict erosion using the Universal Soil Loss Equation (USLE) Model, for sedimentation using the Stanford Sediment model. The analysis of the rate due to erosion, done by non linear regression analysis. The analysis shows that the settlement has an average of 115,85%, plantation 245,50% and sedimentation level 1,017,93 m3 / year. Sedimentation was tested on both sides with a 95% confidence level on the modeled sediment data. Conclusions to tackle erosion using a community-based Terracing Mekar land arrangement model that collaborates with elephant grass and vetiveria.